PENGGUNAAN MODEL PjBL UNTUK MENINGKATKAN KREATIVITAS MAHASISWA DALAM MEMBUAT MEDIA PEMBELAJARAN MATEMATIKA - Dede Trie Kurniawan (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
This study aimed to analyze the level of achievement of the objectives in improving the use of the model PPA creativity mathematics student teachers to create media-based learning of local culture Cirebon. One of the skills that must be owned by prospective teachers of mathematics are capable and able to prepare and use instructional media in the process of teaching and learning activities in class. One of the subjects that prepare prospective teachers of mathematics, in order to have a good competence in the use of instructional media, is Multimedia learning of mathematics subject for third level students with 2 credits point. Culture and local wisdom of Cirebon can be used as one form of media innovative learning in mathematics. It is time for local wisdom cirebon be a source of learning for students. Through the course of learning media is expected student teachers can get to know the culture. The introduction of local culture to students urgently needed so that they can live their culture and themselves. The activities of creative thinking in question is how the students will be the link between learning theory, knowledge of instructional media and cultural wisdom of Cirebon